2011
DOI: 10.1515/jpem.2011.033
|View full text |Cite
|
Sign up to set email alerts
|

Primary pigmented nodular adrenocortical disease: a case report in a 7-year-old girl

Abstract: Primary pigmented nodular adrenocortical disease (PPNAD) is a rare cause of Cushing syndrome in children, often occurring in association with Carney complex. We report a case of Cushing syndrome due to isolated non-familial PPNAD. The child presented with typical clinical characteristics, growth retardation and obesity. Liddle ' s test was positive but micronodular appearance was not evident on CT scan and MRI; selective venous sampling revealed higher cortisol concentrations in the right adrenal vein. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The current diagnostic criteria include skin lentigines, myxomas, and other endocrine and nonendocrine tumors [ 15 ]. Generally, this disease occurs in late adolescence or early adulthood, but a few case reports describe it in younger children [ 7 , 16 ]. Inactivating mutations in the regulatory subunit of type 1 alpha of the protein kinase A (PRKAR1A) gene have been identified in most of the patients with PPNAD [ 1 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current diagnostic criteria include skin lentigines, myxomas, and other endocrine and nonendocrine tumors [ 15 ]. Generally, this disease occurs in late adolescence or early adulthood, but a few case reports describe it in younger children [ 7 , 16 ]. Inactivating mutations in the regulatory subunit of type 1 alpha of the protein kinase A (PRKAR1A) gene have been identified in most of the patients with PPNAD [ 1 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Young et al found AVS to be helpful for deciding treatment strategy in ten patients with ACTH-independent CS and bilateral adrenal masses [10] and, recently, Ueland et al found that four of fourteen patients with MACS and bilateral adrenal lesions had unilateral cortisol hypersecretion [8]. Otherwise, the diagnostic value of AVS in this context is limited to case reports [1119].…”
Section: Introductionmentioning
confidence: 99%